Flocculation Performance and Shearing Capacity Study on Al30 Morphology in Polyhydroxy Aluminium - Jiang, S.J.; Feng, X.R.; Li, X.E.; Xiang, P.; Sheng, G.S. (Asian Journal of Chemistry, 2013)
As a newly discovered polyaluminum morphology after Al13, Al30 is the highest charge cation of polyhydroxy aluminum so far. By comparative analyzing synthetic Al30, Al13 and commercial polyaluminum chloride, test results show that Al30 has optimal coagulation effect by contrasting turbidity, UV254 removal efficiencies and electric neutralization capacity. The particle size analysis of flocculated kaolin micro particles shows that the three flocculants can combine with kaolin particles below 10 μm. The floc size in Al30 is the largest, followed by Al13 and then polyaluminum chloride, which further proved the advantage of Al30 in flocculation process. The conventional jar test and the monitoring technique of floc size online are employed to investigate the shearing capacity of the flocs formed by Al30. It is found that remixing can make the broken flocs fully recovered and the particle size of recovered flocs are greatly increased, especially in Al30.